Exploring the Teaching Readiness of Bael Graduates: Bridging Knowledge and Practice - Alos, Blesie Joy Albis; Gumalwid, Micah Bogayon; Pelila, John Rey Osben (Universitas Kapuas, 2025)
Although Bachelor of Arts in English Language Learning (BAEL) graduates have diverse career options, many are drawn to teaching. This path remains underexplored in terms of their experiences and challenges. This study aimed to explore their motivations, challenges, and level of success in pursuing teaching as a career. Using a qualitative, phenomenological design, the researchers interviewed 16 BAEL graduates from a state university in the Cordillera Administrative Region, Philippines. The findings revealed that BAEL graduates are motivated to teach by personal growth, a passion for learning, and meaningful connections with others. However, despite their strong language skills, many encounter difficulties in classroom management and applying appropriate teaching methods due to limited pedagogical training. These gaps affect their job satisfaction and sometimes lead them to shift careers outside of teaching. The study concludes that teaching remains a viable path for BAEL graduates, with some finding fulfillment and long-term commitment in the profession. Although the study recommends conducting a needs assessment before on-the-job training (OJT) to help students identify career preferences. It is also suggested that integrating teaching methodology courses and providing targeted training on instructional strategies strengthen their readiness for teaching roles.